Study on the morphology-controlled synthesis of MnCO3 materials and their enhanced electrochemical performance for lithium ion batteries. Issue 41 (6th October 2016) - Wang, Lei; Sun, Yuanwei; Zeng, Suyuan; Cui, Chuansheng; Li, Haibo; Xu, Shuling; Wang, Huaisheng
Abstract : In this work, monodispersed and high quality crystalline MnCO3 micro-peanuts and MnCO3 nano-shuttles were prepared by a simple hydrothermal method. Abstract : In this work, monodispersed and high quality crystalline MnCO3 micro-peanuts and MnCO3 nano-shuttles were prepared by a simple hydrothermal method. A growth mechanism was proposed to elucidate the influence of reactant components on the morphology and size of the prepared MnCO3 samples. Both structures were employed as active electrode materials in lithium ion batteries. The electrochemical performance of the obtained MnCO3 samples was examined by analyzing the cyclic voltammograms, galvanostatic charge–discharge, rate performance and electrochemical impedance. At a current rate of 250 mA h g −1, the reversible capacity of the MnCO3 nano-shuttle electrode after 500 cycles was 605 mA h g −1, while that of the MnCO3 micro-peanut electrode was 463.4 mA h g −1 . The results indicated that the MnCO3 samples synthesized by this method presented wonderful electrochemical properties, which could be used as promising active materials in lithium ion batteries.